WHEAT-BASED INTERCROPPING: A REVIEW - M. Aziz; A. Mahmood; M. Asif; A. Ali (Journal of Animal and Plant Sciences, 2015)
The world’s population is increasing rapidly, and in order to feed it, one of the most attractive strategies is to increase productivity per unit area of available land or to increase the land area under production, which seems shrinking day by day. Therefore, to maximize land use and production, the ultimate goal of agriculture, namely yield, intercropping is an advanced agronomic technique that allows two or more crops to yield from the same area of land. Better utilization of resources and reduced weed competition minimize the risk of food shortages by enhancing yield stability. Several factors can affect intercropping: plant density, sowing time, the maturity of a crop, the selection of crop that is compatible with another as well as farmers’ and the region’s socioeconomic conditions. In intercropping, the land equivalent ratio (LER) is used to measure the productivity of land. Since wheat is the most important cereal around the world and is most suitable for intercropping, this review focuses on wheat-based intercropping.
Keywords: intercropping; Wheat; land equivalent ratio; weeds; pests; resource utilization